Natural Language Generation: Algorithms and Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Natural Language Generation (NLG) is a subfield of artificial intelligence and computational linguistics that focuses on the automatic generation of natural language text. NLG has a wide range of applications in various fields, including content generation, virtual assistants, business intelligence, and healthcare. This paper provides an overview of NLG techniques and algorithms, including rule-based NLG, template-based NLG, statistical NLG, and neural NLG. It also explores the applications of NLG in different fields, highlighting its role in automated journalism, personalized content creation, virtual assistants, and data storytelling. Furthermore, the paper discusses the current challenges in NLG, such as naturalness, ambiguity handling, and scalability, and examines emerging trends and future directions in NLG, including advancements in neural NLG models, integration with other AI technologies, and ethical considerations. Overall, this paper aims to provide a comprehensive understanding of NLG and its impact on modern society.